Assessments of the Emission Contributions from an Ultra-Supercritical Coal-Fired Power Plant to Ambient PM2.5 in Taiwan - Yi-Cheng Lin; Fang-Yi Cheng; Yi-Ju Lee; Thi-Thuy-Nghiem Nguyen; Chuen-Jinn Tsai; Huan-Cheng Wen; Cheng-Hung Wu; Wei-Chieh Chang; Chung-Chi Huang (Aerosol and Air Quality Research)
Abstract An ultra-supercritical (USC) coal-fired power plant was built to replace the old subcritical (SC) unit in the Linkou power plant (LPP) in northern Taiwan and has been in operation since 2016. Compared to the old SC power generator, the renovated unit (USC + emission control) can reduce SOx, NOx, and TSP emissions by 65%, 87% and 77%, respectively. Enhancing thermal efficiency can significantly reduce air pollutant emissions; however, its impact on ambient air pollutant concentrations under various meteorological conditions is rarely studied. To clarify the issue, we utilized the Community Multiscale Air Quality (CMAQ) model to estimate the contributions of the emissions from old and renovated LPP on the ambient PM2.5 concentrations in Taiwan. During the one-month study period, the LPP upgrade can reduce the PM2.5 concentrations to more than 10 µg m−3 for a severe PM2.5 episode when the weak wind persisted for several days. The reductions were most significant in northern Taiwan. Even with the substantial emission reductions through the advanced USC units, the LPP emissions contribute considerably to the PM2.5 concentrations, with a maximum reaching 5.1 µg m−3 (10.3%). This study quantitatively assesses the environmental burden that a USC coal-fired power plant places on the ambient PM2.5 concentrations.